2015
DOI: 10.1001/jamadermatol.2014.5263
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bullous Pemphigoid and Malignant Neoplasms

Abstract: Bullous pemphigoid (BP) is the most common autoimmunemediated subepidermal blistering skin disease and occurs mostly in elderly persons. The association of malignant neoplasms with BP has been controversial. 1 This study compared the incidence of cancer in patients with BP with that of the ageand sex-matched general population. with BP were matched with persons in the Singapore Cancer Registry and Death Registry to identify those who had cancer and/or had died. Person-years were accrued from BP diagnosis until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 8 publications
2
24
0
3
Order By: Relevance
“…Nevertheless, a causal relation has only been demonstrated in few cases [ 7,8 ] . A recent cohort study in Singapore found no signifi cant increase in the incidence of cancer among 359 patients with BP compared to the general population [ 4 ] . A British study followed a cohort of almost three million patients with cancer for a 12-year period.…”
mentioning
confidence: 94%
“…Nevertheless, a causal relation has only been demonstrated in few cases [ 7,8 ] . A recent cohort study in Singapore found no signifi cant increase in the incidence of cancer among 359 patients with BP compared to the general population [ 4 ] . A British study followed a cohort of almost three million patients with cancer for a 12-year period.…”
mentioning
confidence: 94%
“…The fact is that this disease may play an important role in BP patients, especially since major drugs used to treat hypertension such as diuretics, ACE inhibitors or spironolactone can provoke BP. 6,13,[20][21][22] Among other comorbidities, single studies have demonstrated the association of BP with diabetes. [23][24][25] To confirm or reject the abovementioned discrepancies, the aim of this study was to assess the relationship between BP and selected comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported conditions are neurological diseases, cardiovascular diseases and diabetes . An association between BP and malignancies is suspected, although no such connection has been confirmed, despite several studies . Recently, however, a clear association of BP with haematological malignancies has been established by a study of about 1,700 BP patients based on data from a health insurance company .…”
Section: Introductionmentioning
confidence: 99%